Deposit-Refundon Labor : A Solution to Equilibrium Unemployment? - Heijdra, Ben (IMF Working Papers; Working Paper ;, 2000)
The paper studies the employment effects of a deposit-refund scheme on labor in a simple search-theoretic model of the labor market. It is shown that if a firm pays a deposit to the government when it fires a worker, to be refunded when it employs the same or another worker, the vacancy rate increases and the unemployment rate declines. However, the scheme introduces rigidities in the labor market that may be undesirable in countries wanting to liberalize their labor markets.